Sustainable Use of the Southern Seas of Russia in the Context of Climatic, Environmental and Technogenic Challenges - Sergey M. Shapovalov; Evgeniia A. Kostianaia (Проблемы постсоветского пространства, 2018)
The southern seas of Russia are of paramount importance for the development of the economy, shipping, recreational zones, and tourism. Development of the port infrastructure, intensification of gas and oil production and transportation, development of tourism along with natural and climatic factors have a strong impact on ecosystems of seas. All of this complicates sustainable development of the region and sustainable use of marine resources. This article examines the climatic, ecological and technogenic challenges associated with sustainable use of the southern seas of Russia. Effective solving of such problems requires an integrated approach, interaction between scientists, representatives of authorities, environmental organizations, business representatives, port and marine services in the framework of Integrated Coastal Zone Management and Marine Spatial Planning.